Benazepril in dogs with asymptomatic mitral valve disease - Brennan, Marnie L.; Stavisky, Jenny (BMJ Publishing Group, 2015)
BestBETs for Vets are generated by the Centre for Evidence-based Veterinary Medicine at the University of Nottingham to help answer specific questions and assist in clinical decision making. Although evidence is often limited, they aim to find, present and draw conclusions from the best available evidence, using a standardised framework.